PROTECTION OF BASE GENEP: COMMUNAL INTELLECTUAL PROPERTY FROM BALI - Dwijayanthi, Putri Triari; Dewi Kasih, Desak Putu; Dewi, Linda Yunita; Balqis, Kinanti (Kertha Semaya : Journal Ilmu Hukum, 2025)
The purposes of this research are to review the implementation of Article 3 paragraph (2) PP 56/2022 regarding the obligation to inventory Communal IP in Bali and analyze the base genep inventory process from Bali as Communal IP in supporting tourism activities. This research is socio-legal research, namely multi-disciplinary and interdisciplinary research that uses several approaches, namely: statutory approach; fact approach and analytical approach. Based on the above explanation, it can be concluded that the Implementation of Article 3 paragraph (2) of PP 56/2022 has been implemented but still needs to be improved. This is because not all types of Communal IP in Bali have been successfully inventoried. Therefore, synergistic cooperation is needed between stakeholders to carry out the mandate of Article 3 paragraph (2) of PP 56/2022. The Base Genep inventory process as one of the Communal IP in supporting tourism activities in Bali begins with conducting normative research by reviewing several provisions of laws and regulations regarding the protection of Communal IP. Starting from the State’s obligation to inventory, maintain and preserve Communal IP. The inventory process is continued by looking for sources that explain the history or origin of the recognition of base genep as a spice in Bali. The source that explains the composition of base genep is the Lontar Dharma Caruban. Base genep can be classified as Communal IP considering that its existence has been passed down from generation to generation as traditional knowledge regarding the processing of Balinese specialties. The purposes of this research are to review the implementation of Article 3 paragraph (2) PP 56/2022 regarding the obligation to inventory Communal IP in Bali and analyze the base genep inventory process from Bali as Communal IP in supporting tourism activities. This research is socio-legal research, namely multi-disciplinary and interdisciplinary research that uses several approaches, namely: statutory approach; fact approach and analytical approach. Based on the above explanation, it can be concluded that the Implementation of Article 3 paragraph (2) of PP 56/2022 has been implemented but still needs to be improved. This is because not all types of Communal IP in Bali have been successfully inventoried. Therefore, synergistic cooperation is needed between stakeholders to carry out the mandate of Article 3 paragraph (2) of PP 56/2022. The Base Genep inventory process as one of the Communal IP in supporting tourism activities in Bali begins with conducting normative research by reviewing several provisions of laws and regulations regarding the protection of Communal IP. Starting from the State’s obligation to inventory, maintain and preserve Communal IP. The inventory process is continued by looking for sources that explain the history or origin of the recognition of base genep as a spice in Bali. The source that explains the composition of base genep is the Lontar Dharma Caruban. Base genep can be classified as Communal IP considering that its existence has been passed down from generation to generation as traditional knowledge regarding the processing of Balinese specialties.